Stress-strain distributions through the thickness of thick walled filament wound polymer composite tube under internal pressure loading. - Salit, Mohd Sapuan; Sahari, Barkawi; Abdalla, F. Hamed; Megat Ahmad, Megat Mohamad Hamdan (2011)
Three dimensional analysis of thick walled filament wound composite tube under internal pressure loading have been explained and presented. The composite tube layers were of balanced and symmetric arrangement about the mid surface of the laminate. The stress and strain distributions through the tube thickness were predicted using monolithic thick cylinder theory with linear elastic orthotropic laminate properties. The analysis is presented for thick shell composite tube under internal pressure for different loading modes by changing the boundary conditions applied such as closed end, open end and combined loading of internal pressure and axial loading. Also theoretical analysis for determining the values for all the elastic constants needed for three dimensional stresses and strains of filament wound tube from the properties of unidirectional fiber reinforced epoxy resin have been included and presented. The stress distribution throughout the thickness of the laminate is ass! umed to be constant. In applying the theory to thicker walled tubes it is necessary to consider the different states of stress and strain on the inside and outside surfaces and to consider the effect of radial stress. The analysis was presented for three dimensional cases and presented in general form so that it can be easily implemented on a computer program. Numerical example was presented and used for closed end condition and the results obtained were compared with the results obtained from Composite-Pro package. The obtained results from the analysis were in a very good agreement with that obtained from Composite-Pro package and very small difference was found among them.